COMPARISON OF DEVELOPED AND PREVIOUSLY PUBLISHED UNIVARIATE MODELS FOR ESTIMATING EROSIVITY IN A COUNTRY WITH MEDITERRANEAN RAINFALL REGIME - & Karim, Keya (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Information on the degree of water erosion is of imperative importance to professionals who are engaged in reducing soil losses via implementing soil conservation measures. Soil Conservation requires the knowledge of the factors controlling soil loss. Rainfall erosivity is one of the major controlling factors inducing water erosion. To achieve this objective, several univariate models were developed to estimate the rainfall erosivity in the upper part of Iraq. The database for models development was based on rainfall data of different time scales obtained from 25 stations distributed across the study region. The explanatory variables encompassed annual rainfall (P), Fournier index (FI), modified Fournier index (MFI) and precipitation concentration index (PCI). Additionally, the performance of a host of previously published univariate models were evaluated. Most of these models were derived for countries with Mediterranean rainfall regimes. It was observed that neither FI nor the PCI approaches were effective in capturing the variability of rainfall erosivity in the study area. Overall, the annual rainfall based models outperformed the Fournier and modified Fournier based models. The results also indicated that among eight developed models, the quadratic and linear forms of annual rainfall based models ranked first and second respectively. Additionally, the test of performance of a host of previously published models revealed they have restricted applications in Iraq.